Business Collective Action: An Integrative Review and Framework - Buchanan, Sean; Højgaard Christiansen, Lærke; Yue, Lori Qingyuan; Kroezen, Jochem (Journal of Management Studies, 2026)
Business collective action (BCA) has long been a topic of interest to management scholars. However, our theoretical understanding of this important phenomenon has been hindered by its fragmented development in the literature. To address this shortcoming, we conduct a comprehensive review of BCA across a wide range of disciplines in management, including corporate political activity, private regulation, strategic management, and organizational institutionalism. Based on this review, we develop an integrative framework that identifies the triggers, outcomes, and internal political arrangements associated with BCA. In doing so, we help develop a common vocabulary that unites different market and non‐market forms of BCA, thus deepening our understanding of the role of business collective action in society.